Research on the design of analytical communication and information model for teaching resources with cloud‐sharing platform. Issue 2 (21st January 2021) - Zheng, Wang; Muthu, BalaAnand; Kadry, Seifedine Nimer
Abstract: The recent growth in the adoption by several organizations of cloud computing services has created the challenge to determine their performance of information model. The ability of cloud computing systems to provide the required services in line with the quality of service and service level agreement constraints is a major problem for cloud service providers and consumers. To that end, it is possible to develop the means of ensuring that the desired levels of success are achieved in simulated environments. In the eventual stage of commissioning and running cloud computing, this will reduce the disrupted service and performance degradation problems using analytical communication and information model of cloud technology. However, several modelers and simulators for simulating cloud computing systems are available in conventional research. This paper, therefore, provides a critical assessment with state of the art cloud computing modeling and simulation frameworks. It compares the prominent frameworks of simulation regarding application programming interface features, programming flexibility, operating system requirements, services supported, and licensing needs with 95% reliability. It offers recommendations to the researchers, administrators, and managers of cloud computing systems regarding the choice of the most appropriate framework.